1988
DOI: 10.1111/j.2042-3306.1988.tb04646.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, location and classification of 371 third carpal bone fractures in 313 horses

Abstract: Summary The medical records and radiographs of all horses with a third carpal bone fracture admitted to The Ohio State University Veterinary Hospital from 1979 to 1987 were reviewed. Three hundred and seventy‐one fractures were found in 313 horses; 57 per cent were Standardbreds, 41 per cent were Thoroughbreds, and only 1.6 per cent were Quarterhorses. All were young racehorses (average age = 3.1 years). Third carpal fractures occurred more frequently in the right limb (60 per cent) than the left limb (40 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 2 publications
7
64
2
Order By: Relevance
“…The predominance of left-sided injuries in this report is notable and differs from previous reports of sagittal plane slab fractures of the third carpal bone [1,2]. Laterality of some orthopaedic injuries is recognised in racehorse populations and is primarily influenced by track configuration.…”
Section: Discussioncontrasting
confidence: 86%
“…The predominance of left-sided injuries in this report is notable and differs from previous reports of sagittal plane slab fractures of the third carpal bone [1,2]. Laterality of some orthopaedic injuries is recognised in racehorse populations and is primarily influenced by track configuration.…”
Section: Discussioncontrasting
confidence: 86%
“…The limb prevalence is consistent with nonfatal third carpal bone fractures [55][56][57][58][59] and fatal scapular fractures in Thoroughbred and Quarter Horse racehorses. The limb prevalence is consistent with nonfatal third carpal bone fractures [55][56][57][58][59] and fatal scapular fractures in Thoroughbred and Quarter Horse racehorses.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, unilateral carpal injuries were more commonly seen in the right limb than in the left limb. Other studies have reported a predominance of carpal fractures in the right limb (Schneider et al 1988;Ramzan and Palmer 2010). The reason for this is unclear, but could be influenced by the direction of training.…”
Section: Discussionmentioning
confidence: 92%